1161 Tasimelteon Shows Persistence Of Efficacy In Improving Sleep Disturbances In Patients With Smith-Magenis Syndrome (SMS) In Open-Label Extension Study. (27th May 2020) - Brooks, J; Gibson, M; Kite, K; Czeisler, E; Fisher, M; Xiao, C; Polymeropoulos, C; Polymeropoulos, M
Abstract: Introduction: Smith-Magenis Syndrome (SMS) is a rare (1/15, 000 - 25, 000 births) neurodevelopmental disorder resulting from an interstitial deletion of chromosome 17p11.2, or from a point mutation in the RAI1 gene. Severe sleep disorder is almost universal in patients with SMS and poses a significant challenge to patients and their families. Tasimelteon improved sleep symptoms in a randomized, double-blind, two-period, crossover study; and here we show that this effect persists for up to four years in an open-label extension. To our knowledge, this is the largest interventional study of SMS patients to date. Methods: Following the 4-week crossover study, all eligible participants had the option to enroll in an open-label extension. 31/39 (79.4%) of all individuals who participated in the efficacy study have continued on tasimelteon treatment. Participants in the open-label extension provided daily diary sleep quality (DDSQ), and daily diary total sleep time (DDTST) measures via parental post sleep questionnaire and characterized behavior using the Aberrant Behavior Checklist (ABC). Results: In the open-label extension, tasimelteon continued to show improvement in the primary endpoints of 50% worst sleep quality (mean = 0.7, SD = 0.94) and 50% worst total nighttime sleep duration (mean = 53.3, SD = 59.01) when compared to baseline. Tasimelteon also improved overall sleep quality (mean=0.7, SD=0.83) and overall total nighttime sleep duration (mean = 51.9, SD=53.03). ABC scores also improved with tasimelteon (mean= -16.3, SD = 15.82). Conclusion: Tasimelteon continues to demonstrate persistence in efficacy (longest approximately 4 years) with similar magnitudes observed in the 4-week crossover study for sleep quality and total sleep time. Interestingly, daytime behavior also demonstrates long-term improvement in patients with SMS treated with tasimelteon. These results further confirm tasimelteon as a novel therapy for the treatment of sleep disorders in patients with SMS and may provide benefit for behavioral symptoms. Support: This work was supported by Vanda Pharmaceuticals Inc.